Trend behaviour of Malaysia Consumer Price Index: evidence from national database (2003-2022) - Nurulkamal Masseran,; Nazihah Ruzelan,; Nur-Firyal, R., (Penerbit Universiti Kebangsaan Malaysia, 2024)
The Consumer Price Index (CPI) is a general indicator used to measure price changes over time. The Malaysia CPI is published using a base year of 2010. This study aimed to identify the significant trend behavior in the Malaysia CPI series for the period 2003–2022. The main question of the paper is whether there exists any difference in trends between the main and overall CPI variables? If so, is the difference significant? If so, how strong or weak is the magnitude of its trend? This is analyzed empirically through five statistical analysis methods involving the serial correlation analysis, Mann–Kendall test, Mann–Kendall sequential test, Sen’s-T test, and Sen’s estimator. Overall, we conclude that there is a significant upward trend for 11 of the 13 variables, while two variables, which are Transportation and Communication, showed no significant monotonic trend. The results of this study provide insight into a better understanding of the behavioral trends of the CPI in Malaysia. This study can help policymakers to understand the importance of increasing expenditure into certain sectors in order to have better production and with this implementation, the trend of inflation rate can be better understood.